ACC.20: Impact of social media at the virtual scientific sessions during the COVID‐19 pandemic. Issue 9 (3rd July 2020) - Mackenzie, Graham; Gulati, Martha
Abstract: Background: The COVID‐19 pandemic led to the American College of Cardiology (ACC) Annual Scientific Session 2020 (ACC.20) being held as a virtual event. Hypothesis: Social media activity around a virtual event might be quite different to that of a physical meeting. The goal of this study was to assess impact of ACC.20 through Twitter and compare it to ACC.19. Methods: Data were extracted using NodeXL, with analysis in Excel. Results: ACC.20‐related tweeting was demonstrated globally. However tweeting and participants fell substantially for ACC.20. Tweeting, participation and tweet views were overestimated by the most widely used social media analysis tool used at medical conferences (Symplur). Conclusion: Comparing the 2019 and 2020 Scientific Sessions, the global cardiology community continued to communicate despite COVID‐19, but with reduced social media activity potentially due to the briefer format, no physical interaction and private virtual chatroom during live sessions, reducing visibility of new cardiology research findings.